Urgensi Reformasi Kebijakan Mengenai Persaingan Usaha Dalam Pasar Digital - Herman, KMS; Hartati, Titin; Amrullah, Amrullah; Kristiani, Enny (Pascasarjana UDA, 2023)
This study aims to analyze the implementation of competition regulation in the digital market with an empirical legal approach, which combines sociological legal analysis to understand the impact and challenges of regulation in social life and the digital economy. By relying on literature studies as a method of data collection, this study examines various legal sources, documents, and related literature to explore the main issues that arise in regulating competition, including monopoly, data misuse, and consumer protection. Qualitative analysis methods are used to evaluate and interpret the data collected, with the aim of identifying obstacles faced in the implementation of existing regulations and the urgency of forming more responsive and adaptive policies to create a healthy and sustainable digital market. This study is expected to provide appropriate policy recommendations to support fair and inclusive competition in the digital sector.